1993
DOI: 10.1016/0014-5793(93)80116-c
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation of deoxycytidine kinase

Abstract: Deoxycytidine kinase enzyme activity and deoxycitidine kinase mRNA content were determined at different positions of the cell cycle in permanent cell lines. There was no variation of deoxycytidine kinase activity during the cell cycle in two cell lines, whereas in two other lines the enzyme activity was induced (IO-and 15-fold) at the GUS boundary. In contrast, the level of deoxycytidine kinase mRNA never displayed any cell cycle-dependent changes. The decay of enzymatic activity was measured after addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…3) (mean of all elutriations 78%). In general, the separation data were very comparable to earlier obtained results with the same or similar cells [18]. Since the quality of separation was that comparable, we concluded that any differences possibly occuring during the cell cycle regulation between the studied cell lines would not be caused by experimental variations.…”
Section: Separation Of Cells In Different Phases Of the Cell Cycle Bysupporting
confidence: 87%
See 1 more Smart Citation
“…3) (mean of all elutriations 78%). In general, the separation data were very comparable to earlier obtained results with the same or similar cells [18]. Since the quality of separation was that comparable, we concluded that any differences possibly occuring during the cell cycle regulation between the studied cell lines would not be caused by experimental variations.…”
Section: Separation Of Cells In Different Phases Of the Cell Cycle Bysupporting
confidence: 87%
“…Separation of cell cycle phases by centrifugal elutriation was performed as described [18]. The elutriation system consisted of a Beckman J2-21 M centrifuge and a JE-6B rotor eqipped with the standard separation chamber.…”
Section: Centrifugal Elutriationmentioning
confidence: 99%
“…This is in contrast to studies on crude protein extract of human muscle and brain that contain very low levels of dCK [5,6]. The reason for the discrepancy is not known, but it has been suggested that expression of dCK may be regulated at the post‐transcriptional level in certain cell types [19]. It is presently not known whether the lymphoblast predominant expression of dCK is regulated at the transcriptional or post‐transcriptional level and further studies will be required to clarify this issue.…”
Section: Discussionmentioning
confidence: 62%